MFN2 Deficiency Impairs Mitochondrial Transport and Downregulates Motor Protein Expression in Human Spinal Motor Neurons - Mou, Yongchao; Dein, Joshua; Chen, Zhenyu; Jagdale, Mrunali; Li, Xue-Jun (Frontiers in Molecular Neuroscience, 2021)
Charcot-Marie-Tooth (CMT) disease is one of the most common genetically inherited neurological disorders and CMT type 2A (CMT 2A) is caused by dominant mutations in the mitofusin-2 (MFN2) gene. MFN2 is located in the outer mitochondrial membrane and is a mediator of mitochondrial fusion, with an essential role in maintaining normal neuronal functions. Although loss of MFN2 induces axonal neuropathy, the detailed mechanism by which MFN2 deficiency results in axonal degeneration of human spinal motor neurons remains largely unknown. In this study, we generated MFN2-knockdown human embryonic stem cell (hESC) lines using lentivirus expressing MFN2 short hairpin RNA (shRNA). Using these hESC lines, we found that MFN2 loss did not affect spinal motor neuron differentiation from hESCs but resulted in mitochondrial fragmentation and dysfunction as determined by live-cell imaging. Notably, MFN2-knockodwn spinal motor neurons exhibited CMT2A disease-related phenotypes, including extensive perikaryal inclusions of phosphorylated neurofilament heavy chain (pNfH), frequent axonal swellings, and increased pNfH levels in long-term cultures. Importantly, MFN2 deficit impaired anterograde and retrograde mitochondrial transport within axons, and reduced the mRNA and protein levels of kinesin and dynein, indicating the interfered motor protein expression induced by MFN2 deficiency. Our results reveal that MFN2 knockdown induced axonal degeneration of spinal motor neurons and defects in mitochondrial morphology and function. The impaired mitochondrial transport in MFN2-knockdown spinal motor neurons is mediated, at least partially, by the altered motor proteins, providing potential therapeutic targets for rescuing axonal degeneration of spinal motor neurons in CMT2A disease.